Pendekatan Tafsir Fiqhi dalam Menafsirkan Al-Qur’an: Analisis Karakteristik dari Kitab-Kitab Tafsir Fiqhi dalam Perspektif Hukum Islam - Mustafa Syam, Muhammad Frayoga; Athoillah; Khosim, Ali (PT. Meja Ilmiah Publikasi, 2026)
This article examines the Islamic jurisprudence (fiqh) approach to interpreting the Qur'an through an in-depth study of the methodology and characteristics of the interpretation contained in Al-Qurtubi's monumental work, Al-Jami` li Ahkam al-Quran. The study focuses on how Al-Qurtubi combines Islamic jurisprudence (fiqh) with Islamic exegesis (tafsir) to explain Qur'anic verses related to sharia laws in a detailed and structured manner. The method used in this interpretation emphasizes understanding the legal context, Islamic jurisprudence principles, and the integration of evidence from the Qur'an, hadith, and the opinions of previous scholars. The results of the study indicate that Al-Qurtubi's interpretation has systematic and comprehensive characteristics in explaining Islamic law, thus becoming a primary reference for scholars and researchers in the fields of interpretation and fiqh. This study also highlights the contribution of Islamic jurisprudence (fiqh) interpretation in enriching the understanding of the Qur'anic text, especially in the context of the application of Islamic law.